Apical Cyst Theory: a Missing Link - George T.-J. Huang (Wolters Kluwer Medknow Publications, 2010)
Introduction: The mechanism of the formation of apical cyst has been elusive. Several theories have long been proposed and discussed speculating how an apical cyst is developed and formed in the jaw bone resulting from endododontic infection. Two popular theories are the nu-tritional deficiency theory and the abscess theory. The nutri-tional deficiency theory assumes that the over proliferated epithelial cells will form a ball mass such that the cells in the center of the mass will be deprived of nutrition. The abscess theory postulates that when an abscess cavity is formed in connective tissue, epithelial cells proliferate and line the preexisting cavity because of their inherent tendency to cover exposed connective tissue surfaces. Based on the nature of epithelial cells and the epithelium, nutri-tional theory is a fairy tale, while abscess theory at best just indi-cates that abscess may be one of the factors that allows the stratified epithelium to form but not to explain a mechanism that makes the cyst to form. The hypothesis: Apical cyst formation is the result of proliferation of resting epithelial cells, due to inflammation, to a sufficient number such that they are able to form a polarized and stratified epithelial lining against dead tissues or foreign materials. These stratified epi-thelial lining expands along the dead tissue or foreign materials and eventually wrap around them as a spherical sac, i.e. a cyst. The space in the sac is considered the external environment separating the internal (tissue) environment - the natural function of epithelium. Evaluation of the hypothesis: This theory may be tested by introducing a biodegradable device able to slowly release epithelial cell mitogens in an in vivo environment implanted with epithelial cells next to a foreign object. This will allow the cells to continuously proliferate which may form a cystic sac wrapping around the foreign object.